The Effect of Instagram Media @ngajilagi.id in Increasing People's Alquran Reading Ability - Sepriasa, Anita; Helena, Helena; Iskandar, M. Yakub (International Journal of Multidisciplinary Research of Higher Education, 2020)
This research aims to analyze changes in people's ability to read the Quran through Instagram media @najilagi.id. This research was conducted using quantitative methods with a survey approach. The data source was taken using a questionnaire from 1,123 respondents who were followers of followers active Instagram account @najilagi.id, all data was then analyzed descriptively. There are twelve points that are measured in order to read the Quran properly and correctly. The results of the research show that there are changes in a person's ability to read the Quran. The results of this research can be used as initial data for subsequent researchers in studying different issues related to this problem as well as various other issues that are relevant to this context.